The Protein Kinase CK2 Mediates Cross-Talk between Auxin- and Salicylic Acid-Signaling Pathways in the Regulation of PINOID Transcription - Armengot, Laia (PLoS One, 2016)
The protein kinase CK2 is a ubiquitous and highly conserved enzyme, the activity of which is vital for eukaryotic cells. We recently demonstrated that CK2 modulates salicylic acid (SA) homeostasis in Arabidopsis thaliana, and that functional interplay between CK2 and SA sustains transcriptional expression of PIN-FORMED (PIN) genes. In this work, we show that CK2 also plays a key role in the transcriptional regulation of PINOID (PID), an AGC protein kinase that modulates the apical/basal localization of auxin-efflux transporters. We show that PID transcription is up-regulated by auxin and by SA and that CK2 is involved in both pathways. On the one hand, CK2 activity is required for proteosome-dependent degradation of AXR3, a member of the AUX/IAA family of auxin transcriptional repressors that must be degraded to activate auxin-responsive gene expression. On the other hand, the role of CK2 in SA homeostasis and, indirectly, in SA-driven PID transcription, was confirmed by using Arabidopsis NahG transgenic plants, which cannot accumulate SA. In conclusion, our results evidence a role for CK2 as a functional link in the negative cross-talk between auxin- and SA-signaling.